2015
DOI: 10.2459/jcm.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effects of renin and aldosterone on right ventricular function in hypertension

Abstract: Isolated hyperreninemia or hyperaldosternism determines a similar impairment of the right ventricular function, whereas their combination is further detrimental. Renin and aldosterone may represent early biomarkers of right ventricular dysfunction in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“… 21) These bio-humoral mechanisms (most notably RAAS) are related to eccentric and concentric LVH patterns 23) as well as the major effect of RAAS on RV remodeling. 24) The interaction of the sympathetic nervous system, the RAAS, and insulin sensitivity, which causes LV and RV hypertrophy, diastolic dysfunction, and deformation impairments, may explain the connection between LV geometry and RV remodeling. The interdependence of the ventricles is especially important in explaining this connection.…”
Section: Discussionmentioning
confidence: 99%
“… 21) These bio-humoral mechanisms (most notably RAAS) are related to eccentric and concentric LVH patterns 23) as well as the major effect of RAAS on RV remodeling. 24) The interaction of the sympathetic nervous system, the RAAS, and insulin sensitivity, which causes LV and RV hypertrophy, diastolic dysfunction, and deformation impairments, may explain the connection between LV geometry and RV remodeling. The interdependence of the ventricles is especially important in explaining this connection.…”
Section: Discussionmentioning
confidence: 99%
“…This might be linked to the influence on the right ventricular systolic function via the helical muscle bundle, interventricular septum, and pericardium shared by the two ventricles, which increases with the LVMI ( 16 ). In addition, the SBP might affect the right ventricular free wall longitudinal strain as follows: when the blood pressure is elevated, various vasoactive substances mediated by activating the renin-angiotensin-aldosterone system could induce fibrosis and degeneration of the pulmonary vascular wall and intima, further affecting the right ventricular systolic function ( 29 , 30 ). Soylu et al ( 31 ) found a remarkably higher plasma aldosterone level in patients with concentric hypertrophy compared with patients with normal geometric and concentric remodeling, which might lead to different right ventricular myocardial mechanics for different left ventricular geometric patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperaldosteronism might further aggravate right ventricular dysfunction, which has been shown in studies with conventional echocardiography, when measured as right ventricular myocardial performance index (RIMP) and tricuspid annular plane systolic excursion (TAPSE) [ 57 , 58 ]. Right ventricular–pulmonary arterial uncoupling can be assessed as the ratio of TAPSE to pulmonary arterial systolic pressure.…”
Section: Right Cardiac Evaluationmentioning
confidence: 99%